FACTORS TO INCREASE SALES TURNOVER OF ORNAMENTAL FISH THROUGH DIGITAL MARKETING - Muhammad Mujib Baidhowi; Hotman Hotman; Hidayat Darussalam (Scientia: Jurnal Hasil Penelitian, 2022)
The development of technology and digital media in Indonesia is very rapid, the rapid development of technology in the digital world and the internet certainly also has an impact on the business world. Various activities such as small to large scale businesses take advantage of this development to run their businesses, one example is by using digital marketing. In this study, researchers wanted to examine the factors of increasing sales turnover of ornamental fish through digital marketing and whether using application-based digital marketing affects sales turnover. In this study, researchers sought to gather relevant sources, namely by interview methods and documentation. Following qualitative descriptive research, a study that focuses on field research. In sampling interviews, researchers choose to use the Snowball Sampling technique where samples are obtained through the process of rolling from one respondent to another. Based on the results of the research conducted, researchers present an analysis of data obtained through field research that the effectiveness of the application of digital marketing is influenced by several factors, namely target market, technology, content, budget, and media used. The digital marketing strategy used by Koi ornamental fish entrepreneurs is a Facebook application where the use is easy and does not require large capital that the scope of the market is wide, many people can see and search for products offered, thus impacting increasing buyers and making sales turnover increase.